ETOS KERJA DAN KONTRIBUSI IBU RUMAH TANGGA PEMULUNG TERHADAP EKONOMI KELUARGA (STUDI DI TPA MUARA FAJAR PEKANBARU) - Reka Faddilah; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The work ethic is the character of a person or group of people in the form of will or willingness in work accompanied by high spirit to realize the ideals, while the contribution is money donation or support to help in the form of material that is the family economy. Here the authors take the Work Ethic and the Contribution of Housewife Scavengers to the Family Economy which the authors use descriptive quantitative methods using a simple random sampling technique sampling method in which respondents amounted to 86. The results showed that there are factors that affect the work ethic: 1) Skill Level, (2) Morale, (3) Productivity and also (4) Contributions of Housewives Scavengers, (5) Total Family Income. The number of women who work to help the family economy makes the work of housewife of high scavenger housewives is obtained based on the amount of contribution given by housewife that is equal to 39,8% with average income equal to Rp. 3,458,627. The lowest contribution given by housewife scavengers is 8.6% or Rp. 1,170,000 and the highest contribution of 66.8% or Rp.7.095.000 they earn only from scavenging activity by working over 7 hours and they are looking for the most easily collected garbage, they also sell the garbage once a week so they can making the distribution of waste by group, making it easy to sell based on the price of waste.Keywords: Working Ethic, Housewife Scavenger, Contribution